SAW Microstrip Front-End for Mobile Communication Systems in the GHz Range - Anemogiannis, Kimon; Russer, Peter; Weigel, Robert; Zimmermann, C. (IEEE MTT-S International Microwave Symposium Digest, 1991, 1991)
The design, fabrication, and performance of a SAW (surface acoustic wave) microstrip front-end circuit in the low GHz range for applications in time division multiple access systems are reported. The front-end consists of a transmitter part (containing a SAW filter for noise suppression, and amplifiers), a receiver part (containing a stripline filter for preselection, a SAW filter, and a low-noise amplifier), and a duplexing circuit. Both the transmitter SAW filter and the receiver SAW filter are low-loss filters with a center frequency of 1.684 GHz, a fractional 3 dB-bandwidth of 3.5% and an insertion loss of 6 dB. The front-end operates at 1.684 and has 1 dB-bandwidth of 30 MHz. The output power at the antenna port is 23 dBm.<>
elib2cris::1512001600,anemogiannis1991
Keywords: mobile communication systems; strip line components; surface acoustic wave filters; time division multiple access; 1.684 GHz; mobile communication systems; low-noise amplifier; low-loss filters